Research progress on the role of Klotho in heart failure - CHAI Yaru, DENG Yuting, DAI Hongyan, GUAN Jun (Jichu yixue yu linchuang, 2023)
Klotho is an anti-aging protein and can be divided into three types: full-length transmembrane Klotho, soluble Klotho and secreted Klotho. Many studies have shown that Klotho is closely related to oxidative stress, inflammatory response, myocardial hypertrophy, fibrosis, autophagy, and mitochondrial dysfunction. It is also involved in the occurrence and development of heart failure. It is expected to provide a new target and direction for the treatment of heart failure.